Proceedings of the 13th International Symposium and 5th Conference on Lameness in Ruminants : 11th - 15th February 2004, Congress and Convention Centre Habakuk, Maribor, Slovenija / president of organising committee, Borut Zemljič ; organising secretary, Špela Zemljic ; preparation of proceedings, Matej Novak ; edited by Borut Zemljič. (2004)
Summary goes here